Palliative treatment with the use of photodynamic therapy of patients with malignant tumors of pancreatobiliary zone complicated by obstructive jaundice - A. E. Tseimakh; A. F. Lazarev; E. L. Sekerzhinskaya; V. A. Kurtukov; A. N. Mitshenko; V. N. Teplukhin; Ya. N. Shoykhet (Biomedical Photonics, 2020)
The paper presents the results of a complex palliative treatment using photodynamic therapy of patients with pancreatobiliary malignancies complicated by obstructive jaundice. In the main group, which included 22 patients, palliative comprehensive treatment was performed using local and systemic photodynamic therapy of pancreatobiliary neoplasms complicated by obstructive jaundice. In the comparison group, consisting of 165 patients, palliative complex treatment of complications was performed without the use of photodynamic therapy. The used photosensitizers were chlorin-based fotoditazin (21 patients) and radachlorin (1 patient). The first step was a systemic PDT. In the course of infusion through a peripheral access into the cubital vein, blood was irradiated externally by laser with monochromatic light with a wavelength of 662–665 nm and a light dose of 1200–1400 J/cm2 . As the second stage of the treatment, 3–5 hours after the end of the infusion, an intraductal PDT was carried out by irradiation with monochromatic light with a wavelength of 662 nm and a light dose of 220 J/cm2 . After the use of local and systemic photodynamic therapy, a statistically significant decrease in the size of the tumor focus in patients with pancreatic malignant neoplasms was established within a week after treatment in the main group according to the ultrasound examination of the abdominal cavity. Restoration of bile excretion into the intestine was noted in 100% of patients with malignant neoplasms of the bile duct and head of the pancreas. We also note an increase in median survival of patients in the main group to 5.9 months compared with 4.7 months in the comparison group.